ANALISIS PENGARUH PERTUMBUHAN PENJUALAN, PERPUTARAN MODAL KERJA DAN LEVERAGE TERHADAP PROFITABILITAS PADA PERUSAHAAN OTOMOTIF YANG TERDAFTAR PADA BURSA EFEK INDONESIA (BEI) TAHUN 2011 – 2016 - Primadayani, Syurti (Jurnal Daya Saing, 2024)
Abstract: This research aimed to find out the effect of the sales growth, working capital turnover and leverage to profitability at automotive company listed on the Indonesia stock exchange (idx). Method of analysis is used was a multiple linear analysis. Research results are obtained, sales growth and working capital turnover partially do not has significant effect to profitability, while the leverage affect significantly to profitability. Hypothesis test simultaneously do not affect significantly to profitability. Finally the author suggested to companies who are investing, so that before making an investment, investors should pay attention to the debt owned by the company. It was proved that leverage gives significant influence towards profitability, so that companies that have a good profitability, it also has good leverage, and the company deserves to be used as a place to invest.